Students' Perceptions Of The Use Of Wordwall Media In Indonesian Language Learning In Class X-U4 At SMAN 1 Anjatan - Rahayu Putri, Ilmiyanti; Astriyani; Wanda Ayu Salsabila; Mahmud (Universitas Swadaya Gunung Jati, 2025)
This study aims to analyze students' perceptions of the use ofWordwall media in Indonesian language learning in class X-U4 atSMAN 1 Anjatan. The research method used is descriptive qualitativewith data collection techniques in the form of questionnaires with 32respondents. The results of the study indicate that Wordwall mediahas a positive impact in creating an interesting, enjoyable, andinteractive learning atmosphere. 62.5% of students strongly agreedand 37.5% agreed that Wordwall makes learning more interesting.Additionally, this medium also helps improve students' motivation,self-confidence, enthusiasm, and awareness of the importance ofIndonesian language lessons. However, only 9.4% of studentsstrongly agreed that Wordwall encourages independent learningoutside the classroom. Thus, while Wordwall is effective in enhancingstudent motivation and engagement in the classroom, its use as a toolfor independent learning requires additional approaches. This studyconcludes that Wordwall can serve as an innovative learning tool toenhance student interest and motivation, particularly in Indonesianlanguage learning